Speech Act Analysis on Abdullah Azwar Anas Presentation in Kick Andy TV Show - Handayani, Gayatri Mayang; Cahyono, Arik Fajar (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This research analyzed the illocutionary speech acts and its function found in the presentation of Abdullah Azwar Anas in Kick Andy TV show. This research aims at describing kinds and functions of speech acts based on the theory emerged by Yule. This research is descriptive qualitative analysis. The data was obtained from video on YouTube and the presentation was transcribed. The data then selected and identified based on the speech act classification. The result of the analysis showed: (a) there were five types of speech act found in the presentation, namely: representative/ assertive, expressive, directive, commissive, and declarative. (b) the most frequent type of speech was representative/ assertive. (c) the functions of the speech act found in Anas’ presentation were to express opinions, give information, give orders either directly or indirectly, and say gratitude and blessing.